Leaf age structures phyllosphere microbial communities in the field and greenhouse - Geyer, Julie K.; Grunberg, Rita L.; Wang, Jeremy; Mitchell, Charles E. (Frontiers in Microbiology, 2024)
The structure of the leaf microbiome can alter host fitness and change in response to abiotic and biotic factors, like seasonality, climate, and leaf age. However, relatively few studies consider the influence of host age on microbial communities at a time scale of a few days, a short time scale relevant to microbes. To understand how host age modulates changes in the fungal and bacterial leaf microbiome on a short time scale, we ran independent field and greenhouse-based studies and characterized phyllosphere communities using next-generation sequencing approaches. Our field study characterized changes in the fungal and bacterial phyllosphere by examining leaves of different relative ages across individuals, whereas the greenhouse study examined changes in the fungal microbiome by absolute leaf age across individuals. Together, these results indicate that fungal communities are susceptible to change as a leaf ages as evidenced by shifts in the diversity of fungal taxa both in the field and the greenhouse. Similarly, there were increases in the diversity of fungal taxa by leaf age in the greenhouse. In bacterial communities in the field, we observed changes in the diversity, composition, and relative abundance of common taxa. These findings build upon previous literature characterizing host-associated communities at longer time scales and provide a foundation for targeted work examining how specific microbial taxa might interact with each other, such as finescale interactions between pathogenic and non-pathogenic species.